ANALYSIS OF CREDIT RELAXATION AND LEGAL PROTECTION PROVIDED BY THE GOVERNMENT TO MSMES DURING THE COVID-19 PANDEMIC - Komang Gede Narottama Nataprawira; I Ketut Westra (Transpublika Publisher, 2022)
This research aims to analyze the government's role in helping micro, small and medium enterprises (MSMEs) and legal protection for MSMEs provided by the government due to the impact of the Covid-19 pandemic. This research uses normative juridical research. The approach used in this research is the statutory approach which examines the regulations or laws related to the legal issues under study. The results of the analysis show that the government's efforts to ease the burden on the victims of Covid-19 are in the form of credit relaxation policy. The targets are those who previously had to apply for relief at the bank. The government solution is in the form of credit relaxation policy by lowering interest rates, increasing loans and converting loans into equity, extending the term of the loan, reducing the principal, increasing the credit limit and reducing interest arrears on loans.